Sharing Circles as a way to facilitate capacity sharing across generations and cultures - Lisa Grosfeld (Zenodo, 2023)
This presentation was part of thesession "Improving intercultural and transdisciplinary collaborations in Arctic research by better understanding the value of capacity sharing - Special ECR and Arctic youth version" atthe Arctic Science Summit Week 2023. In this presentation we present an approach towards starting intercultural and transdisciplinary dialogue in the frame of the EU project Arctic PASSION. The format of a Sharing Circle for early career scientists and Arctic youth will be presented and discussed. This activity was driven by the project’s principle surrounding intercultural capacity sharing. The concept of the Sharing Circle has been co-created from the beginning with early career scientists and the Indigenous community where the event will take place. Discussions held in indoor and outdoor settings will help facilitate transdisciplinary dialogue and two-way, cross-cultural knowledge sharing. It is hoped that the next generation of Arctic scientists will gain an understanding of the importance and complexity of relationship building and early dialogue early in research processes. Thus, leading to more inclusive, cross-sectoral and cross-cultural research in the future. Lessons learned from this Sharing Circle will help guide Arctic PASSIONs progress forward and will hopefully impact future research collaborations beyond the group of participants, as these will spread the messages in their home countries afterwards. See more information here: https://arcticpassion.eu/sharingcircle/